A Rare Case of Neuroendocrine Tumor Following Radical Nephrectomy - Ishaq, Muhammad Rozaqy; Febriansyah, Nafis Audrey; Soetojo, Soetojo (Folia Medica Indonesiana, 2022)
Highlights: • Rare occurrence of a large, well-differentiated primary renal neuroendocrine tumor in a young man. • Identifying primary renal NET from the workup and histological examination of renal tumors needs to be done to understand more of this infrequent type of tumor. Abstract: Neuroendocrine Tumors (NETs) are a diverse range of neoplasms with various biological and histologic features and therapeutic responses. The prevalence of primary renal carcinoids is scarce worldwide. At the moment, complete surgical resection is the primary treatment against primary neuroendocrine tumors of the kidney. Nephrectomy followed by the lymph node dissection is a standard procedure for localized primary renal NETs. Since renal carcinoid tumor is extremely rare, we decided to present a unique case of a 25-years-old male with neuroendocrine renal carcinoid tumor following radical nephrectomy. The results indicated a solid, solitary tumor verified on the frozen section because a postoperative CT–scan showed a recurring mass in the renal fossa following radical nephrectomy. The case emphasized the need to investigate primary renal NET in the workup and histological examination of renal tumors and also contributed to our understanding of this infrequent clinical entity.